Penerapan Algoritma Apostolico Giancarlo Pada Pencarian Fasilitas Umum di Provinsi Aceh Berbasis Android - Muasir Pagan; Efori Buulolo (Forum Kerjasama Pendidikan Tinggi, 2021)
Public Facilities are facilities built by the government for the benefit of the general public. The problem that is often faced in Aceh Province is the difficulty of knowing the location of Public Facilities in Aceh Province due to the difficulty of the signal, many Public Facilities are not yet registered and mapped on Google Maps. Mobile Phone is one of the fastest growing technologies. Mobile Phone was originally used to send letters and make calls, but has now evolved into a smartphone that has the function of searching for a location. Apostolico Giancrlo works by comparing each index of keyword characters with the String character being examined. The search for strings in the Apostolico Giancarlo algorithm starts with pre-processing keywords. Pre-processing of keywords. This pre-processing is done to look at the index number of strings that are checked for each keyword character